Giant Penile Lymphedema Caused by Chronic Penile Strangulation with Rubber Band: A Case Report and Review of the Literature - Shunsuke Hori; Yozo Mitsui; Hidenori Iwai; Toshihiro Tai; Hideyuki Kobayashi; Koichi Nakajima; Koichi Nagao (Case Reports in Urology)
We treated a 65-year-old Japanese man with a giant penile lymphedema due to chronic penile strangulation with a rubber band. He was referred to our hospital with progressive penile swelling that had developed over a period of 2 years from chronic use of a rubber band placed around the penile base for prevention of urinary incontinence. Under a diagnosis of giant penile lymphedema, we performed resection of abnormal penile skin weighing 4.8 kg, followed by a penile plasty procedure. To the best of our knowledge, this is only the seventh report of such a case worldwide, with the present giant penile lymphedema the most reported.